A knowledge broker for collaboration and sharing for SIDS: the case of comprehensive disaster management in the Caribbean*. Issue 1 (2nd January 2019) - Rao, Lila; McNaughton, Maurice
ABSTRACT: Knowledge sharing can be hindered by barriers that prevent the free flow of information, especially across organizational and other boundaries. Therefore information produced at one location might not be available to entities elsewhere even if there are benefits to sharing this information. This can often lead to 'reinventing the wheel' and wasted investments in duplicating resources and ultimately will lead to the development of knowledge silos . Information technologies can be used to address this problem as they provide opportunities to lower the barriers to knowledge sharing and increase collaboration. This need for knowledge sharing and collaborative technologies can be important for Small Island Developing States (SIDS) within particular regions that are exposed to similar environmental and economic issues that can hinder their development. Although each SIDS may have Knowledge Resources that it uses to address its own issues, there would be benefits to collaborating and sharing these resources to collectively tackle these regional issues. Even when there is a willingness to share and collaborate and entities have been established to foster this collaboration, there is a void in the availability of tools and technologies needed to support collaboration and sharing of resources. This paper describes the research that has been done to help fill this void by designing and developing a technological solution, a Knowledge Broker, for the identification and sharing of Knowledge Resources that may be spread across various locations (e.g. countries). The Design Science Research methodology was used to develop the Knowledge Broker architecture, which provides a single point of access to the knowledge resources within a particular domain. A critical component of this Knowledge Broker is a common, online interactive vocabulary of the domain of interest which provides the terms which are used to describe and search for the knowledge resources available. The Knowledge Broker was evaluated using informed arguments and an illustrative scenario in the Comprehensive Disaster Management domain in the Caribbean region. The initial evaluations that have been reported in this paper indicates that the Knowledge Broker has the potential to increase the efficiency of solving regional issues through the sharing of knowledge resources.